THE FEATURES OF RELIGIOUS EDUCATION IN IN THE WORKS OF KAREKIN I CATOLICOS (Education in the 21st Century, 2023)
SummaryIn the comprehensive process of human formation, religion and moral principles and spiritual values related to it have their unique importance.Religious education and upbringing are one of the most important elements of the educational system.It should be noted that in the works related to the history of Armenian pedagogy, religious or moral education and upbringing partially addressed but they didn't separate the two but presented them in a unified context.The problems of religious education have always been in the His Holiness' attention. This is the reason why throughout his spiritual activity, Karekin I initiated and implemented number of programs, which were the basis for the formation of the spiritual and moral value system of the young generation.In his works His Holiness the Patriarch presents his vision of the educational policy of effective organization of religious education.During his enthronement in Holy Etchmiadzin, Catholicos Karekin I managed to transform the educational system for training future clergymen, founded centres of spiritual education and gave impetus to the activity of spiritual seminaries for the benefit of future generations.